Cryopreservation increases DNA fragmentation in spermatozoa of smokers - ERCAN, FERİHA (ELSEVIER GMBH, 2013)
Smoking causes subfertility due to deterioration of spermatozoa including decreased concentration and abnormal morphology. Although evidence on the deleterious effects of smoking on spermatozoa parameters is well known, its interference with cryopreservation is not clear. This study aimed to investigate the effects of cryopreservation on sperm parameters and DNA fragmentation in non-smokers and smokers. Semen samples were obtained from 40 normospermic male volunteers of whom 20 were non-smokers and 20 smokers. Samples were analyzed in terms of motility, concentration, morphology, and DNA fragmentation before freezing and 1 and 3 months after freezing and thawing. Ultrastructural alterations were investigated by transmission electron microscopy. Sperm morphology seemed to be more affected after cryopreservation in samples obtained from smokers. Ultrastructural examination showed alterations in the integrity of the membranes and increased subacrosomal swelling. Before freezing, the increase in DNA fragmentation rate in smokers was not statistically significant compared to that of non-smokers. However, after thawing, the DNA fragmentation rates were significantly high in both non-smokers and smokers compared to their respective rates before freezing. The extent of the increase in DNA fragmentation rate was significantly higher in smokers after thawing compared to that of non-smokers. In conclusion, cryopreservation causes alterations in membrane integrity and increases DNA fragmentation, thus triggering relatively negative effects on the sperm samples of smokers compared to that of non-smokers. (C) 2012 Elsevier GmbH. All rights reserved.
Keywords: Spermatozoa; Cryopreservation; Smoking; DNA fragmentation; Ultrastructure; CIGARETTE-SMOKING; SPERM CHROMATIN; OXIDATIVE STRESS; HUMAN SEMEN; PARAMETERS; INTEGRITY; MOTILITY; PLASMA; DAMAGE; TEMPERATURE